KELUARGA SAKINAH DI ERA SCROLL: MENJAGA KEHANGATAN RUMAH TANGGA DARI GANGGUAN GADGET - Khullatussa'adah Khullatussa'adah (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2025)
Advances in digital technology have brought about significant changes in patterns of family communication and interaction. Gadgets, which were originally intended to make people’s lives easier, now often act as a barrier to emotional closeness within the household. The phenomenon of ‘endless scrolling’ on social media has led to a decline in the quality of communication between partners and between parents and children. This article discusses the concept of the sakinah family from an Islamic perspective, as well as the challenges arising from excessive gadget use. This study employs a literature review method, analysing various sources on the sakinah family, family psychology, and the impact of digital technology. The findings indicate that uncontrolled gadget use can trigger domestic conflicts, reduce the quality of communication, and weaken the family’s spiritual values and sense of togetherness. Therefore, efforts are needed to foster a healthy digital culture through intensive communication, restrictions on gadget use, strengthening shared worship, and instilling Islamic values within the family. In this way, the concept of the ‘sakinah’ family can still be realised amidst the rapid tide of digitalisation.